Smartphone fitness applications used by runners: For what reason? - Aroni, Andre Luis; Batista, Marco; Machad, Afonso Antonio [UNESP]; Gomes, Antonio Rui (Univ Alicante, 2019)
The aim of this study was to explore which smartphones applications features have most been appreciated by runners. This descriptive and exploratory study consisted of 278 respondents from Brazil and Portugal. A survey composed of demographic and closed questions was developed and distributed via social media. Findings revealed that 40.8% of the runners in Brazil prefer the calories spent as main feature, while also 40.8% of the participants in Portugal prefer the heart rate control. The difference between the preferred features in Brazil and Portugal indicates that more cross-cultural research is needed to unravel the biopsycho-social mechanisms that might explain why members of some groups have different opinions than other ones.
Keywords: Smartphones; Applications; Physical activity; Runners